Room temperature lasing unraveled by a strong resonance between gain and parasitic absorption in uniaxially strained germanium - Gupta, Shashank (2018)
A complementary metal-oxide semiconductor compatible on-chip light source is the holy grail of silicon photonics and has the potential to alleviate the key scaling issues arising due to electrical interconnects. Despite several theoretical predictions, a sustainable, room temperature laser from a group-IV material is yet to be demonstrated. In this work, we show that a particular loss mechanism, inter-valence-band absorption (IVBA), has been inadequately modeled until now and capturing its effect accurately as a function of strain is crucial to understanding light emission processes from uniaxially strained germanium (Ge). We present a detailed model of light emission in Ge that accurately models IVBA in the presence of strain and other factors such as polarization, doping, and carrier injection, thereby revising the road map toward a room temperature Ge laser. Strikingly, a special resonance between gain and loss mechanisms at 4%-5% ⟨100⟩ uniaxial strain is found resulting in a high net gain of more than 400cm−1 at room temperature. It is shown that achieving this resonance should be the goal of experimental work rather than pursuing a direct band gap Ge.